The comparison of fire safety management elements in public higher educational library building / Damia Athirah Ajman - Damia Atirah, Ajman (2018)
ibrary is the most frequent places that visited by the student at university, schools and even public library. The main purpose of library is the places for keeping books, journal, articles and other secondary sources for review. Student are attracted to study at the library is because of its calm environment, silent and it help them to focus while doing their work. However, there are some cases of fire outbreaks occurred in the library is due to the problem of occupants such as carelessness, negligence or simply a lack of fire safety awareness that using the library but it also causes due to unconsciousness of measures to be taken in the event of fire. Although the library is equipped with the latest fire safety equipment, the assurance of the occupants cannot be fully guarantee and remains a matter of questions and doubts. In response to this problem, fire safety management has become an important aspect in the daily operations library and this study presents the results of investigation on fire safety management in the library. The objectives of the study are to identify the elements of fire safety management in public higher educational library building in Malaysia and to compare the differences and similarities of fire safety management’s elements in public higher educational library building in Malaysia. This study is aim to study and observe the current fire safety management elements in public higher educational learning building in Malaysia. In order to achieve the objectives of this study, the methodology for conducting this study including of literature review, data collection and analysis of results using interview session. The process of data collection will be design throughout the primary data from respondents by providing some questions through interview to the staff who involved in Fire Safety Department of the library. The findings of this study hoped that it would provide some useful insight on the important elements of fire safety management and help guide to the library users to safeguard their life and property.